Valoración de docentes multigrado sobre un marco que orienta el diseño de unidades STEM integradas - Jiménez-Villarroel, Rodrigo; Medina-Paredes, Jhonny; Castro-Inostroza, Angela; Chávez-Herting, David; Castrelo-Silva, Nicole (Revista Científica, 2022)
The design of STEM units embedded in traditional schooling contexts has been extensively investigated. However, there has been no exploration on how to elaborate this type of proposal in multigrade contexts. This study aims to determine the assessment by a group of teachers on the relevance and feasibility of a framework that guides the design of integrated STEM units in multigrade contexts. Additionally, their perceptions of STEM education and its implementation in these contexts were explored. By using an evaluative research design with a participatory modality in the context of a professional development course in STEM, focus groups were implemented throughout the sessions, and a questionnaire was elaborated and applied at the end of professional development. Findings suggest that the analyzed framework is relevant and feasible, but some stages could be better integrated. Teachers are open to learn in order to implement this type of education, which they see as an opportunity to contextualize and integrate knowledge. Still, they report needing more constant and lasting support so as to apply it in their classrooms.